2008
DOI: 10.1016/j.neurobiolaging.2006.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Arrestins and two receptor kinases are upregulated in Parkinson's disease with dementia

Abstract: Arrestins and G proteins-coupled receptor kinases (GRKs) regulate signaling and trafficking of G protein-coupled receptors. We investigated changes in the expression of arrestins and GRKs in the striatum of patients with Parkinson's disease without (PD) or with dementia (PDD) at post mortem using Western blotting and ribonuclease protection assay. Both PD and PDD groups had similar degree of dopamine depletion in all striatal regions. Arrestin proteins and mRNAs were increased in the PDD group throughout stria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 106 publications
3
66
0
Order By: Relevance
“…An inverse correlation between GRK2 and arrestin protein levels has also been described in other hypothyroid organs (37) and in macrophages sustainedly stimulated through Toll-like receptors (38). However, a simultaneous increase in GRK2 and ␤-arrestin levels is observed after myocardial infarction (39), in Parkinson disease (40) or during acquisition of analgesic tolerance in the brain (41), indicating that such functional interplay is more complex. Interestingly, up-regulation of GRK2 protein caused by dopamine depletion in animal models of Parkinson disease is reverted upon restoration of receptor signaling with L-dopa treatment (42).…”
Section: Discussionmentioning
confidence: 86%
“…An inverse correlation between GRK2 and arrestin protein levels has also been described in other hypothyroid organs (37) and in macrophages sustainedly stimulated through Toll-like receptors (38). However, a simultaneous increase in GRK2 and ␤-arrestin levels is observed after myocardial infarction (39), in Parkinson disease (40) or during acquisition of analgesic tolerance in the brain (41), indicating that such functional interplay is more complex. Interestingly, up-regulation of GRK2 protein caused by dopamine depletion in animal models of Parkinson disease is reverted upon restoration of receptor signaling with L-dopa treatment (42).…”
Section: Discussionmentioning
confidence: 86%
“…Our earlier work demonstrated that in response to opiate stimulation, ␤-arrestin-1 recruits P300 and activates gene transcription (10). Up-regulation of ␤-arrestin-2 was observed in the striatum of patients of Parkinson's disease with dementia (11). Recent study has revealed that dopaminergic signaling induces the formation of the ␤-arrestin-2-Akt-PP2A complex and thus modulates the effect of lithium in psychiatric disorders (12,13).…”
mentioning
confidence: 99%
“…Evolution endowed mammals with ϳ1000 different GPCRs (Römpler et al, 2007) that are phosphorylated by seven GRKs (Moore et al, 2007) and a number of other kinases (Budd et al, 2000;Naik et al, 2005;Luo et al, 2008) and interact with four arrestin subtypes (Gurevich and Gurevich, 2006b). Each tissue and cell has a unique complement of receptors (Penn et al, 2001), GRKs and arrestins (Penn et al, 2001;Gurevich et al, 2002;Ahmed et al, 2008a,b;Bychkov et al, 2008) that changes, sometimes quite dramatically, during development (Gurevich et al, 2002, disease (Ahmed et al, 2008a;Bychkov et al, 2008), and drug treatment (Ahmed et al, 2008b). To make matters even more complicated, phosphorylation of the same receptor at different sites (Pals-Rylaarsdam et al, 1997; Lee et al, 2000;Key et al, 2003;Jones and Hinkle, 2008), by different GRKs Ren et al, 2005;Luo et al, 2008), or even by the same GRK to different levels (Vishnivetskiy et al, 2007) generates functionally distinct receptor species that bind arrestins with different biological consequences.…”
mentioning
confidence: 99%